Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0004110.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hemichordates: Development

Abstract: Hemichordates are marine invertebrates consisting of two distinct groups: the solitary enteropneusts, or acorn worms (comprising a few hundred species), and the colonial and tube‐dwelling pterobranchs (comprising 20 or so species). Phylogenetically, hemichordates are the sister group to echinoderms, together composing the Ambulacraria, and share some features with chordates. Hemichordates are thus considered key organisms for addressing the origins of deuterostome and chordate body plans. Unlike the other deut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Due their bilateral symmetry as adults, hemichordates show analogous regeneration patterns with the chordates. This has been proved at molecular level, where gene expression analysis revealed that Hemicordata regeneration requires an independent stem-cell endogenous transdifferentiation, and particular genetic mechanisms (Lowe et al, 2003;Tagawa, 2015, 2018;Miyamoto and Wada, 2015). In Deuterostome, Hemichordate are the only known to regenerate the complete NS of the anterior head-like structure, as Ptychodera flava that has the ability to regenerate their entire NS in 1-4 days (Humphreys et al, 2010;Luttrell et al, 2016).…”
Section: Hemichordatamentioning
confidence: 99%
“…Due their bilateral symmetry as adults, hemichordates show analogous regeneration patterns with the chordates. This has been proved at molecular level, where gene expression analysis revealed that Hemicordata regeneration requires an independent stem-cell endogenous transdifferentiation, and particular genetic mechanisms (Lowe et al, 2003;Tagawa, 2015, 2018;Miyamoto and Wada, 2015). In Deuterostome, Hemichordate are the only known to regenerate the complete NS of the anterior head-like structure, as Ptychodera flava that has the ability to regenerate their entire NS in 1-4 days (Humphreys et al, 2010;Luttrell et al, 2016).…”
Section: Hemichordatamentioning
confidence: 99%